Single-cell and spatial transcriptomics approaches of the bone marrow microenvironment. Issue 2 (March 2020) - Al-Sabah, Jude; Baccin, Chiara; Haas, Simon
Abstract : Purpose of review: The bone marrow is home to hematopoietic stem cells responsible for lifelong blood production, alongside mesenchymal stem cells required for skeletal regeneration. In the bone marrow, a unique combination of signals derived from a multitude of cell types results in the establishment of so-called niches that regulate stem-cell maintenance and differentiation. Recently, single-cell and spatially resolved transcriptomics technologies have been utilized to characterize the murine bone marrow microenvironment during homeostasis, stress and upon cancer-induced remodeling. In this review, we summarize the major findings of these studies. Recent findings: Single-cell technologies applied to bone marrow provided the first systematic and label-free identification of bone marrow cell types, enabled their molecular and spatial characterization, and clarified the cellular sources of key prohematopoietic factors. Large transcriptional heterogeneity and novel subpopulations were observed in compartments previously thought to be homogenous. For example, Lepr + Cxcl12-abundant reticular cells were shown to constitute the major source of prohematopoietic factors, but consist of subpopulations differing in their adipogenic versus osteogenic priming, morphology and localization. These subpopulations were suggested to act as professional cytokine secreting cells, thereby establishing distinct bone marrow niches. Summary: Single-cell and spatially resolved transcriptomics approaches have clarified the molecular identity and localization of bone marrow-resident cell types, paving the road for a deeper exploration of bone marrow niches in the mouse and humans.